Perbedaan Kompetensi Guru BK Lulusan S1 BK dan S1 Non BK - Novitasari, Dian; Wibowo, Mungin Eddy (Universitas Negeri Semarang, 2016)
Educational background guidance and counseling teacher will bring a variaty of considerations related to the competence of teachers guidance and counseling. The purpose of this research was to determine the competence of guidance and counseling teacers who came from graduate guidance and counseling and are not graduate of guidance and counseling at public high scools throughout the disttrict Rembang, and to know is there any difference. The method in this research is survey deskriptif komparatif. The population in this research is all the guidance and counseling teacers atpublic high scools throughout the disttrict Rembang totaled 27 teacers guidance and counseling.The sampling technique used is saturated Sampling. The data collection method used was a questionnaire in the from of a psychological scale. Data analysis using quantitative analysis using descriptive statistics and analysis of different test two-sample t-test independent. The research results showed that the guidance and counseling teacher competence graduate guidance and counseling are included in the catergory of very high (73%) and competence guidance and counseling teachers who are not graduates of guidance and counseling were high (73%). And there are significant differences.